Design of Kansei Engineering System (KES) for the Effectiveness of Product Search Functions in E-Commerce by Emotion Category - Nurlaelasari, Euis; Shofia Hilabi, Sofha; Benny Chiago, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The essence of a product will greatly affect one's interest in the product, as well as will give an idea of the impression of the product. Kansei Engineering is a method of determining product design based on feelings or emotions. The design of the product will be translated into emotions that humans have. A brightly colored plate with a flower shape can be interpreted as a cheerful emotion. This makes humans have an attachment to the product because of emotional connections. Therefore, this research will implement the kansei engineering method for products in e-commerce. These goals are motivated by e-commerce trends that will continue to grow in the future. The results of this study are in the form of a Kansei system design to search products in e-commerce catalogs based on emotions. The conclusion of this research is to be able to arrange the best product search algorithm based on emotions and Kansei system design with the main function of product search based on emotions. Based on the results obtained, further research is expected to use a particular algorithm to automate the knowledge base processing that is needed in KES.